Urgensi Ketersediaan Pelayanan Publik bagi Kesejahteraan Ramah disabilitas di Kota Madiun - Shufya, Fauzi Himma; Pribadi, Farid (Jurnal Dinamika Sosial Budaya, 2023)
Disability groups are people who have deficiencies in carrying out activities in daily life due to a person's physical and psychological factors. The problem of disability is a phenomenon that has received less attention from the public. So that the issue of disability discrimination is increasingly mushrooming and cannot be resolved. Evidence of discrimination against disability groups is reflected in the lack of access and facilities provided to disabled groups. As a result, the problem of discrimination against people with disabilities will still exist. This study uses a qualitative type with a literature study. The analysis of this research uses the structural functional theory of Talcot Parsons. The concept of Talcot Parsons' theory is AGIL (Adaptation, Goal Attainment, Integration, Latent Pattern Maintenance). The data used in this study is secondary data obtained from literature review, mass media news on the internet. The target of this research is Madiun City, East Java. The results of this study are that the City of Madiun is a city that is still low in accessibility to disability groups. It is proven by the provision of facilities that are still minimal, even some facilities will still be discussed in 2021.